Development of nuclear microsatellite markers in Stizophyllum (Bignoniaceae) using next-generation sequencing. Issue 4 (5th August 2019) - Beyer, Maila; Nazareno, Alison Gonçalvez; Lohmann, Lúcia G.
Abstract: Here we developed the first set of nuclear microsatellite markers (nSSRs) for Stizophyllum riparium (Bignoniaceae), a widespread species of Neotropical liana. Thirty-two sets of primers were isolated from a genomic dataset obtained with an Illumina HiSeq Platform, and characterized for 57 individuals of S. riparium from three populations. Nine nSSRs were polymorphic and the number of alleles ranged from eight to 29. The unbiased expected heterozygosity per locus ranged from 0.724 to 0.952 and the polymorphic information content values ranged from 0.717 to 0.944. All nine primer pairs also amplified for two closely related species ( S. inaequilaterum and S. perforatum ). The new set of nuclear markers will be useful for population genetics studies of Stizophyllum as a whole.